ปัจจัยที่สัมพันธ์กับขนาดยาวาร์ฟารินเริ่มต้นของผู้ป่วย ณ โรงพยาบาลจุฬาลงกรณ์ - สุดาพร คูสุวรรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
Warfarin is an oral anticoagulant that is indicated to prevent and treat thromboembolicevents. Warfarin has been used clinically for a long time. There are a lot of research studies butthere is no recommended warfarin starting dose in Thai population. This study aimed to determinefactors associated with the initial dose of warfarin in patients and to evaluate the accuracy ofsimplified warfarin dosing formula. The retrospective descriptive correlational study was conductedat King Chulalongkorn Memorial Hospital. Thai inpatients aged 18 years and over who receivedwarfarin for the first time between January 2015 and December 2020 were enrolled in this study.Data were analyzed by using multiple linear regression analysis to define the correlation with SPSSversion 28.A total of 125 patients were enrolled; 70 were male (56%); average weight was 64.0 + 13.1ks, average age was 61.3 + 14.79 years. The most indication of warfarin were heart valve repair orreplacement. Average warfarin initial dose was 16.89 t 6.46 mg/week. The result showed that factorsrelated to the warfarin dose on the discharge date were weight, hypoalbuminemia, liver function(AST), age over 70 years, hematocrit, and an indication of heart valve repair or replacement. As forcorrelation analysis between the warfarin dose on hospital discharge date and the warfarin dosecalculated from the simplified warfarin dosing formula using age and weight demonstrated a weakcorrelation (r=0.429, p=0.003). When compared to the dose calculated from the multiple linearregression equation generated using weight, liver function (ALT), an indication of heart valve repairor replacement, and over 70 years of age, the values obtained from this equation were moderateto strong correlation with the dose of warfarin on the discharge date (r=0.738, p<0.001).In conclusion, factors associated with the initial dose of warfarin were weight, liver function,age, and an indication of heart valve repair or replacement. This can be applied as a doserecommendation in patients who are starting warfarin for the first time. However, after the patienthas started warfarin, the INR should be monitored, and the dose should be adjusted to the targetrange of treatment.